Barcoded screening identifies nanocarriers for protein delivery to kidney - Luyao Wang; Wen Zhou; Hang Chen; Xiangqian Jia; Peiyuan Zheng; Haolin Jiang; Mengling Wu; Yaning Zhang; Yanchao Ding; Yexi Peng; Rui Zhu; Tiantian Li; et al. (Nature Communications)
Abstract Targeted protein delivery with nanocarriers holds significant potential to enhance therapeutic outcomes by precisely directing proteins to specific organs or tissues. However, the complex interactions between nanocarriers and the biological environment pose considerable challenges in designing effective targeted delivery vehicles. In this study, we address this challenge by leveraging DNA-barcoded high-throughput screening. We construct a nanocapsule library via in-situ polymerization, incorporating various monomers to create nanocapsules with unique surface properties. In vitro and in vivo screening, using female mice, identify nanocapsules with high cell association and different biodistribution. Our investigation into kidney-enriched nanocapsules highlights the crucial role of polymer composition in biodistribution, demonstrating the potential of surface engineering for precise control over nanoparticle distribution. The kidney-enriched nanocapsule successfully delivers catalase, showcasing its therapeutic potential in mitigating cisplatin-induced acute kidney injury. Overall, our study presents an approach for identifying protein delivery vehicles, with the capacity to broaden the application of proteins as therapeutic agents or research tools.